Chronic spontaneous urticaria or autoinflammatory disease? The therapeutic effect of omalizumab in a pediatric patient. (14th December 2018) - Maggio, Maria Cristina; Lucania, Anna; Collura, Mirella; Corsello, Giovanni
Abstract: Chronic spontaneous urticaria (CSU) is a clinical condition characterized by spontaneous or inducible recurrent wheals. This condition may significantly affect quality of life of patients and of their families. Etiology is not identified in 25–85% of cases that are indicated as 'idiopathic', because all diagnostic tests are negative. Autoimmune processes may be present in 30–50% of patients, although a definite etiological diagnosis is seldom possible. Some patients, in fact, have autoantibodies against the high-affinity IgE receptor FcεR1 or IgE. These patients show an increased incidence of anti-thyroid autoantibodies and represent 30–50% of the patients designated as having CSU. Familial cold autoinflammatory syndrome (FCAS) must be distinguished from acquired cold urticaria, which is characterized by a rash occurring within a few minutes after cold exposure, and is often described as 'allergy to cold'. Cold urticaria (CU) is rare in childhood and is not linked to inflammatory markers. The treatment is based on antihistamines. However, in non-responders, a second-line treatment with omalizumab can show efficacy. We describe the clinical case of a 9-year-old-female with recurrent monthly episodes of fever, arthralgia, abdominal pain, and urticaria-angioedema who did not respond to steroids associated with antihistamines, however, showed the complete resolution of the disease with omalizumab.